A short review and a preliminary regeneration study of a commercially important Bangladeshi potato variety: Diamant - Afroz, Samia (BRAC Univeristy, 2018)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Biotechnology, 2018.